2021
DOI: 10.21037/tp-20-181
|View full text |Cite
|
Sign up to set email alerts
|

Counseling for fetal heart disease—current standards and best practice

Abstract: Congenital heart disease (CHD) is the most common cause of major congenital anomalies affecting newborns. Prenatal detection of CHD has been improving continuously during the last two decades due to technical advances and thus optimized fetal cardiac imaging. Besides the in-utero diagnosis of CHD effective parental counseling is an integral part of any Fetal Cardiology Program. However, studies on the most effective techniques are scarce, as well as data on empirical assessment of counseling and its effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Multidisciplinary team counseling can help family members understand precisely and comprehensively the subtype, available management and treatment options, and the long-term prognosis of fetal heart abnormalities and facilitate decision-making [37][38][39]. In keeping with recent researches [21,40], our results con rmed the signi cant impact of a multidisciplinary team approach on the pregnancy outcomes of fetal cardiac defects.…”
Section: Discussionsupporting
confidence: 77%
“…Multidisciplinary team counseling can help family members understand precisely and comprehensively the subtype, available management and treatment options, and the long-term prognosis of fetal heart abnormalities and facilitate decision-making [37][38][39]. In keeping with recent researches [21,40], our results con rmed the signi cant impact of a multidisciplinary team approach on the pregnancy outcomes of fetal cardiac defects.…”
Section: Discussionsupporting
confidence: 77%
“…In summary, our results may serve as paradigm to develop strategies to optimize fetal cardiac care in terms of improving the effectiveness of parental counseling [ 21 , 22 ]. Furthermore, as national guidelines are scarce, our results may be valuable to propose evidence-based strategies and suggest topics to be included during conversation [ 29 ]. In addition, communication skills training for “breaking bad news” in Fetal Cardiology should be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Patients have reported relief and support from nurses after receiving the diagnoses of CHD in their fetus (Bratt et al, 2015;Reid & Gaskin, 2018). Some articles also stressed the importance of continuous, on-going support provided by nurses throughout the patient's pregnancy and beyond (Bratt et al, 2015;Kovacevic et al, 2020b;Kovacevic et al, 2021;Lafranchi & Lincoln, 2015;Lee, 2017). The nurse's presence from preconception to birth allows excellent continuity of care for the patient and family.…”
Section: Recordsmentioning
confidence: 99%
“…In a study of parental counseling needs, parents reported difficulties with "perceived situational control," which Kovacevic et al (2020b) believed could be alleviated with further and continuous support throughout the pregnancy, including by cardiac specialist nurses (p. 6). Providing contact information for nurses who can be available to answer families' questions throughout the pregnancy can "preserve long-term psychological health of parents" (Kovacevic et al, 2021(Kovacevic et al, , p. 2231.…”
Section: Recordsmentioning
confidence: 99%